“A Man of Keen Perceptive Faculties”:∗ Aboobaker Amod Jhaveri, an “Arab” in Colonial Natal, circa 1872-1887 (Historia, 2021)
EnglishAboobaker Amod is generally regarded as the first passenger migrant of Indian origin to settle in Natal. His stay was short but he made a significant religious, economic and social contribution. This short biography of Aboobaker serves as a lens through which to view the migratory experiences of early traders, their association with indentured Indians, networks among traders and relationships between passengers, white settlers and colonial authorities. Passenger migrants came outside of official arrangements between the governments of India and Natal. They came voluntarily at their own expense and were subject to the ordinary laws of the Colony. Aboobaker’s story underscores the manner in which colonial authorities differentiated Indians on the basis of class, the fissures among Indian migrants, importance of family networks in increasing immigration and the importance of religion in shaping Indian lives. This paper also highlights the difficulty and value of using oral history. Many of the legends about Aboobaker which are accepted among his descendants and are repeated in public settings, are not corroborated by “historical facts”. This emphasizes the importance of examining diverse historical sources in reconstructing the past. While testimony from Aboobaker’s family provided the broad outlines of his life, this was augmented by archival sources and contemporary newspapers. This helped to recreate the most likely account of Aboobaker’s early life and settlement in Natal. This endeavour underlines the fact that historical knowledge is always partial and subject to revision.   Afrikaans“A Man of Keen Perceptive Faculties”: Aboobaker Amod Jhaveri, ‘n “Arabier” in Koloniale Natal, circa 1872-1887 Aboobaker Amod word oor die algemeen beskou as die eerste passasier Indiese landsverhuiser wat hom in Natal gevestig het. Sy verblyf was kort, maar nogtans het hy ‘n betekenisvolle godsdienstige, ekonomiese en sosiale bydrae gelewer. Hierdie bondige biografie van Aboobaker dien as ‘n lens waardeur die migrasie belewenisse van vroeë handelaars, hulle verhouding met ingeboekte Indiese arbeiders, onderlinge netwerke tussen handelaars en die verhouding tussen Indiese passasier immigrante, wit nedersetters en die koloniale owerhede bestudeer kan word. Passasier immigrante het onafhanklik van die offisiële ooreenkomste tussen die owerhede van Indië en Natal verhuis. Hulle het vrywillig en op eie koste geïmmigreer en was onderhewig aan die normale koloniale wetgewing. Aboobaker se lewensverhaal onderstreep die wyse waarop die koloniale owerhede tussen Indiërs onderskei het op grond van klas, die gapings tussen Indiese migrante, die rol van familienetwerke by toenemende immigrasie en die belangrikheid van godsdiens in die vorming van Indiërs se lewens. Hierdie artikel dui ook die problematiek verbonde aan, en waarde van die gebruik van mondeling oorgelewerde geskiedenis aan. Vele van die legendes oor Aboobaker wat sondermeer deur sy nageslag aanvaar en in die openbaar herhaal word, word nie deur “historiese feite” gestaaf nie. Die feit beklemtoon die belang daarvan om diverse historiese bronne aan deeglike beoordeling en ondersoek te onderwerp wanneer die verlede herskep word. Waar die getuienis van Aboobaker se familie die breë buitelyne van sy lewe voorsien het, is die res van die prentjie deur argivale bronne en tydgenootlike koerante ingevul. Dit het gehelp om die mees akkurate weergawe moontlik van Aboobaker se vroeë lewe en vestiging in Natal te skep. Hierdie poging toon weer eens dat historiese kennis altyd net gedeeltelike kennis is en altyd aan hersiening ondergeskik bly.
Keywords: Indian traders; Muslims; migration; ethnicity; racism; colonial Natal; Indiër handelaars; Moslems; migrasie; etnisiteit; rassisme; koloniale Natal